PEMODELAN STABILITAS BENDUNG MAROS DENGAN MENGGUNAKAN APLIKASI SAP2000 - Riswal Karamma; Ahmad Syarif Sukri (Informatics Engineering Department of Halu Oleo University, 2019)
Analysis of the stability of the weirs can be compared with the results of the modeling application using SAP2000 stability that can reveal a condition safe and critical of the results of the design of weirs. The results of modeling the structure of maximum voltage-generating dam hold 30.354186 t/m2 occurred in the bottom of the pond while the maximum voltage refuses 16.811126 t/m2 occurred in the top of the outdoor refuse. A load of mud shows a voltage of-4.194299 t/m2 and 2.626117 t/m2, load the normal voltage-generating water 47.18661 t/m2 and 31.412491 t/m2 load voltage-generating flood water 24.214049 t/m2 and 11.098479 t/m2. The results suggested the presence of part of the structure that is experiencing a critical condition. Part of the structure that has the maximum voltage value is the weakest part of the construction area.Keywords—Stabilility,Weir, SAP2000 DOI : 10.5281/zenodo.2652067